Model Pembelajaran RADEC dalam Perspektif Pendidikan Karakter - Suryana, Nana; Sopandi, Wahyu; Budimansyah, Dasim; Ruyadi, Yadi (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research aims to describe the Read, Answer, Discuss, Explain, and Create (RADEC) learning model from a character education perspective. This research uses library research or literature study, namely examining the RADEC learning model and character education using literature that is relevant and supports the research topic. The approach used in the research is a qualitative approach with descriptive methods. Researchers try to explore and provide arguments related to the RADEC learning model from a character education perspective. The results of the findings and discussion show that the RADEC learning model with the syntax Read, Ansew, Discuss, Explain, and Create is in accordance with the character education approach. RADEC is able to bring out student characters such as religious, diligent, disciplined, hard working, and fond of reading, curious, creative, tolerant, cooperative, and democratic, appreciating achievement, friendly, communicative. The emergence of character is patterned in the four character education approaches, namely the values ​​instillation approach, cognitive development approach, values ​​clarification approach, and action learning approach. Through the RADEC learning model, character can be transformed into knowledge, morals and behavior.